Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1063/1.2221526
|View full text |Cite
|
Sign up to set email alerts
|

Formation of nanovoids in high-dose hydrogen implanted GaN

Abstract: The formation of nanovoids upon high-dose hydrogen implantation and subsequent annealing in GaN is investigated by transmission electron microscopy. The epitaxial GaN layers on sapphire were implanted at room temperature with H2+ ions at 100keV with a dose of 13×1016cm−2. Cross section transmission electron microscopy investigations revealed that nanovoids about 2nm in diameter had formed during hydrogen implantation at room temperature while large microcracks (∼150–200nm long) occurred upon annealing (1h at 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 13 publications
3
17
0
Order By: Relevance
“…), as observed earlier by a few studies [16,25,26]. Thus, it is concluded that the III nitrides require higher values of minimum hydrogen dose in comparison to other semiconductors such as Si, Ge, GaAs, SiC and InP for the surface blistering to occur due to their higher radiation resistance.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…), as observed earlier by a few studies [16,25,26]. Thus, it is concluded that the III nitrides require higher values of minimum hydrogen dose in comparison to other semiconductors such as Si, Ge, GaAs, SiC and InP for the surface blistering to occur due to their higher radiation resistance.…”
Section: Resultssupporting
confidence: 62%
“…It is known from the literature that the group III nitrides such as AlN and GaN exhibit very efficient dynamic annealing of the implantation-induced defects [20][21][22][23][24]. In the process of blistering, the implanted hydrogen interacts with the implantation-induced damage inside the semiconductor lattice that ultimately leads to the formation of extended defects such as nanovoids/nanoplatelets [9,10,13,25]. Upon thermal annealing of the hydrogenimplanted semiconductor, these nanovoids/nanoplatelets grow in size and agglomerate together due to the overpressure of hydrogen gas filled within them ultimately leading to the formation of large area microcracks.…”
Section: Resultsmentioning
confidence: 99%
“…These nanovoids upon high temperature annealing lead to the formation of nanocracks and microcracks inside the damage band (Fig. 3) that eventually lead to the formation of surface blisters [12][13][14][15]. .…”
Section: Resultsmentioning
confidence: 99%
“…Hence the nanovoids served as precursors to microcrack formation and were essential for the blistering process. 60,61 In order to achieve thin-film layer transfer, 2-inch-diameter free-standing (FS) GaN wafers were implanted with 100-keV H 2 + ions at a dose of 1.3 9 10 17 cm À2 at room temperature. However, after H-implantation of FS-GaN, the bow of the wafers increased drastically to about 35 lm from an initial value of 1 lm to 2 lm (Fig.…”
Section: Ganmentioning
confidence: 99%